Circularly polarized luminescence of nanoassemblies via multi-dimensional chiral architecture control. Issue 38 (23rd September 2020) - Chen, Wenjie; Ma, Kai; Duan, Pengfei; Ouyang, Guanghui; Zhu, Xuefeng; Zhang, Li; Liu, Minghua
Abstract : Circularly polarized luminescence (CPL) is currently an important chiroptical properties among chiral systems. By tuning the dimensional architectures of nanoassemblies, the CPL properties could be effectively tuned and boosted. Abstract : Circularly polarized luminescence (CPL) materials are currently an important class of chiroptical materials that are attracting increasing interest. Nanoassemblies constructed from chiral or achiral building blocks show great potential for achieving CPL-active nanomaterials with high quantum yields and dissymmetry factors, which is crucial for further applications. In nanoassemblies, the dimensional morphology affects the chiroptical properties significantly since the microscopic packing modes will affect the luminescence processes and chirality transfer processes. In this review, we will show some examples for illustrating the relationship between multi-dimensional morphology and chiroptical properties. Furthermore, with dimensional morphology tuning, higher dissymmetry factors would be obtained. We hope to provide a useful and powerful insight into the design and control of CPL-active nanoassemblies via morphology control.